Beyond Ideology:China-Indonesia Engagement and the Making of the Guided Democracy, 1955-1959 - Kankan Xie (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2016)
China's engagement with Indonesia from 1955 to 1959 was neither ideologically oriented nor realpolitik, but somewhere in between. It happened not only because of the changing domestic political situations or completely subject to the shifting international environment, but was also closely associated with intrinsic social and historical issues that transcended geographical, ideological and ethnic boundaries within and across the two nation-states. To some extent, this e?ective engagement was not a result of Indonesias leaning towards the left, but a reason for itnot in the sense of direct political intervention, but through the pursuit of common identity and interest, which signifcantly shaped the making of Indonesias Guided Democracy.